An overview of biodiesel energy - Abd Halim, Muhamad Fazli; Khalid, Amir; Leman, Abdul Mutalib; Mohamed Sunar, Norshuhaila (Penerbit UTHM, 2020)
Over the last ten years’ attention to biofuels production has increased dramatically and become crucial. One of the main factors is the rise in world oil prices, coupled with the abatement of greenhouse gas emissions and concerns about energy security. Biodiesel is diesel fuel extracted and made out of animal fats, vegetable oils, or recycled restaurant greases. It is harmless, biodegradable, and generate fewer air pollutants than conventional-based diesel. This paper will be summarized the overview of biodiesel including. competitiveness of biodiesel, ii. biodiesel production and iii. engine performance using biodiesel.